Community Engagement for Realization of Regenerative Village Entrepreneurial Groups: Pathway to Sustainable Banana Entrepreneurship in Alue Krueng Village, Aceh Jaya Regency - Aulia, Muhammad Reza; Sahputra , Deni; Fathin , Silmi; Anggraini , Putri; Agusrianda, Agusrianda; Putri , Gebrina; Azzahra , Misya (Universitas Ahmad Dahlan, 2024)
Background: Regenerative agriculture and banana-based entrepreneurship can restore soil health and boost the economy in Alue Krueng Village. Contribution: This initiative assessed community engagement in sustainable farming and banana waste utilization in Aceh Jaya Regency. Method: The Participatory Action and Action Research (PALAR) method guided community assistance.. Results: The program has transformed the local economy by turning banana waste into viable business ventures and equipping the community with enhanced knowledge and skills in regenerative agriculture. Institutional support and marketing strategies have laid a solid foundation for ongoing growth and success in the banana-based industry. Conclusion: The program in Alue Krueng Village enhanced local entrepreneurship and economic growth by promoting regenerative banana cultivation and turning agricultural waste into value-added products. It serves as a scalable model for sustainable rural development, emphasizing the importance of institutional support, market strategies, and government involvement in fostering resource-based entrepreneurship.